Economic analysis of rapid multiplex polymerase chain reaction testing for meningitis/encephalitis in pediatric patients. (9th January 2018) - Duff, Steve; Hasbun, Rodrigo; Ginocchio, Christine C; Balada-Llasat, Joan-Miquel; Zimmer, Louise; Bozzette, Samuel A
Aim: We assessed the possible economic impact of a rapid test in pediatric patients with suspected community-acquired meningitis/encephalitis.Materials & methods: Modeling simulated diagnosis, clinical decisions, resource use/costs of standard of care (SOC) and two cerebrospinal fluid testing strategies using FilmArray ® (FA), a US FDA-cleared system that provides results in approximately 1 h.Results: Pathogens detected by FA caused approximately 75% of cases, 97% of which would be accurately diagnosed with FA. Mean cost/case ranged from 17, 599 to 22, 025. Syndromic testing is less expensive than SOC. Testing all suspected cases yielded greater savings (3481/case) than testing only those with abnormal cerebrospinal fluid (2157/case).Conclusion: Greater economic benefits are achievable with syndromic testing of all cases, rather than SOC or targeted syndromic testing.